2023
DOI: 10.1139/cjz-2022-0129
|View full text |Cite
|
Sign up to set email alerts
|

Prehibernation swarming in temperate bats: a critical transition between summer activity and hibernation

Abstract: In this contribution to Dr. Brock Fenton's Festschrift, we briefly reflect on Dr. Fenton's seminal works examining bat swarming behaviour in Ontario and use these reflections as a launch pad to conduct a global review on autumn swarming in bats, and underlying hypotheses to explain this behaviour. Our review frames the swarming period as a time of critical transitions, during which bats must balance multiple life history trade-offs, and we consider how various intrinsic and extrinsic factors may contribute to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 123 publications
0
9
0
Order By: Relevance
“…Differences in seasonal behaviours could also contribute to observed response. In the fall, bats must put on sufficient fat reserves but are also engaged in fall swarm mating behaviours (Fraser & McGuire, 2023). In the spring, bats emerge from hibernation and females must recover their body condition and migrate to maternity roosts before giving birth (Norquay & Willis, 2014).…”
Section: (A) (B) (C)mentioning
confidence: 99%
“…Differences in seasonal behaviours could also contribute to observed response. In the fall, bats must put on sufficient fat reserves but are also engaged in fall swarm mating behaviours (Fraser & McGuire, 2023). In the spring, bats emerge from hibernation and females must recover their body condition and migrate to maternity roosts before giving birth (Norquay & Willis, 2014).…”
Section: (A) (B) (C)mentioning
confidence: 99%
“…Although we found that summer distributions are biased by sex, autumn pell-mell movements appear to be undertaken by both sexes (see Supporting Results section). We expect that male bats may be incentivized to search for mating opportunities at higher latitudes than their summering grounds, either by seeking mates directly or traveling to hypothesized lekking or swarming locations (22, 23, 59). Female bats must also be incentivized to move in late summer, potentially to either seek out or avoid mating events, or possibly to pursue optimal prey after an interval of low mobility while raising young.…”
Section: Discussionmentioning
confidence: 99%
“…In reality, immergence into hibernation and emergence from hibernation are not discrete in populations of hibernating bats. In both autumn and spring, bats likely use a mixed strategy with short bouts of torpor or hibernation interspersed with energy replenishing foraging (Fraser & McGuire, 2023). It is therefore more realistic to think of the winter season as a transition from summer behaviors as food becomes sporadic, into a deeper winter torpor, and then back into a transitory period as food becomes increasingly available in spring.…”
Section: Methodsmentioning
confidence: 99%
“…In reality, immergence into hibernation and emergence from hibernation are not discrete in populations of hibernating bats. In both autumn and spring, bats likely use a mixed strategy with short bouts of torpor or hibernation interspersed with energy replenishing foraging(Fraser & McGuire, 2023).…”
mentioning
confidence: 99%